A Model of Digital Inequality in the Knowledge Society: The Case of Slovenia - Mitja Dečman (Central European Public Administration Review)
The knowledge society defines information technology (IT) as the crucial factor in accessing knowledge today. At the same time, knowledge itself represents the precondition for using technology. This paradox is linked with the concept of digital inequality, which examines the difference between people in society and includes various levels, such as physical access to technology, possession of the skills to use it, social and cultural influences, and relations between and within these levels. Although the phenomenon of digital inequality is at least two decades old, it has an important role even today. The following paper discusses the notion of digital inequality and links it to information technology access and use in the society. Using the results of 1568 questionnaires completed by a representative sample of Slovenian citizens in 2016, it develops a five-level model that indicates the factors influencing the reasons for the inequalities. The results show that the survey misses the top two levels of the model, but indicate that gender differences are diminishing while income differences significantly influence internet availability, digital skills, and IT use. The results suggest changes in policies that countries should implement to achieve digital inclusion for everyone and consequently the highest possible use of IT and the benefits for society that come with it.